2012
DOI: 10.9753/icce.v33.structures.32
|View full text |Cite
|
Sign up to set email alerts
|

Granular Open Filters on a Horizontal Bed Under Wave and Current Loading

Abstract: Rubble mound coastal structures typically contain granular filters in one or more layers. These filters are normally geometrically tight (to prevent material washout), often difficult to realize in the field, and expensive. An alternative is a geometrically open filter (i.e. a large ratio of the size of toplayer material and underlayer material), designed in such a way that it fulfills its filter functions with only minimal base material loss or settlement. Potential applications of open filters include bed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This assumption has been confirmed in the present study, which showed initiation of motion for i/i cr ≈ 1. Similar observations were already made in Wolters & Van Gent (2012). For more information on the Forchheimer relation as applied to granular filters, reference is made to Wolters (2012) and Van Gent (1995).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…This assumption has been confirmed in the present study, which showed initiation of motion for i/i cr ≈ 1. Similar observations were already made in Wolters & Van Gent (2012). For more information on the Forchheimer relation as applied to granular filters, reference is made to Wolters (2012) and Van Gent (1995).…”
mentioning
confidence: 49%
“…It is noted that the described loading parameter also appear to be applicable to current loading (see e.g. Wolters & Van Gent, 2012).…”
Section: Erosion Predictionmentioning
confidence: 99%
“…Although recent studies have examined the stability of a scour protection that contains a single stone cover above an additional filter layer (Sumer and Nielsen 2013;Nielsen et al 2013;De Schoesitter et al 2014), to the authors' knowledge, so far no research has been performed in the investigation of a scour protection design that integrates the functions of the filter and cover layer in one single layer. Wolters and van Gent (2012) and Schürenkamp et al (2014) performed experiments on the stability of geometrically open filters, which are characterized by a large ratio of the size of top-layer material and sublayer material. While these studies focused on the interface stability between base and filter layer and on the transport of base material, the erosion stability of a single-layer filter against external hydrodynamic loading was not considered.…”
Section: Introductionmentioning
confidence: 99%